T Cells and Acute Kidney Injury: A Two-Way Relationship - Dellepiane, Sergio; Leventhal, Jeremy S.; Cravedi, Paolo (Frontiers in Immunology, 2020)
Acute Kidney Injury (AKI) complicates up to 10% of hospital admissions substantially increasing patient morbidity and mortality. Experimental evidence supports that AKI initiation and maintenance results from immune-mediated damage. Exogenous injury sources directly damage renal cells which produce pro-inflammatory mediators recruiting immune cells and furthering kidney injury. Many AKI studies focus on activation of innate immunity; major components include complement pathways, neutrophils, and monocytes. Recently, growing evidence emphasizes T lymphocytes role in affecting AKI pathogenesis and magnitude. In particular, T helper 17 lymphocytes enhance tissue injury by recruiting neutrophils and other inflammatory cells, while regulatory T cells conversely reduce renal injury and facilitate repair. Intriguingly, evidence supports local parenchymal-T cell interactions as essential to producing T cell phenotypic changes affecting long-term kidney and patient survival. Herein, we review T cells effects on AKI and patient outcomes and discuss related new therapeutic approaches to improve outcomes of affected individuals.